Al-Yasār al-Islāmī: Iṭlālah ‘Āmmah - Naṣr Abū Zaid (Al-Jami'ah: Journal of Islamic Studies, 2004)
Islamic thought develop rapidly as the progress of Islam in the classical era especially when Islam facing modernity nowadays. In general, the discourse of Islamic thought ranges from the “left” to the “right”. The term "left" is used for political movement and changes which defends the right and interest of poor individual, i.e. vulnerable and oppressed people. This mainstream fight against social in justice caused by economics and politics, such as the tendency of elites to support certain communities in any forms and to neglect others. In general it can be stated that leftist movements aim to develop society, toward freedom of thought and civilized, and also employ logic as a way of life and thinking method. Although it seems very excellent for the society, however it also has some disadvantages such as it could harm personal freedom. Meanwhile the “right" is used for political movement and changes which demand for private freedom. It seem that the "right' movement more flexible than the “left” one to protect personal freedom of thought especially freedom of faith, freedom of thought etc. To conclude, the "right" movement is more conservative to protect tradition.